Computer Literacy of Government Employees Correlated to Job Performance and Satisfaction - M. C. P. Lagon, Rose; C. Pagunsan, Mercedes; G. Paredes, Nodelyn; B. L. Esposo, Joe; F. Lanceta, Elsa; S. Garcia, June; A. M. Cebal, Kent; D. Catamin, Vincent (Journal of Multidisciplinary in Social Sciences, 2023)
This correlational study aimed to determine the relationships among computer literacy, job satisfaction, and job performance of 121 government employees in the Municipality of Calinog, Iloilo, Philippines who were selected using total enumeration during the year 2018. This study utilized the adapted Perception of Computer Technology Competencies, Performance Evaluation, and An Index of Job Satisfaction. The research used statistical tools such as the mean, standard deviation, and Pearson’s r where alpha was set at 0.01. The findings of the study revealed that the participants were “Skilled” in their computer literacy, “Fairly Satisfied” in their work, and had a “High” level of job performance. Furthermore, the study revealed that computer literacy, job satisfaction, and job performance were positively correlated. It is suggested that the government employees be continuously provided by relevant trainings, seminars, and workshops because such trainings have positive bearings on their job satisfaction and performance.